2019
DOI: 10.1002/tox.22885
|View full text |Cite
|
Sign up to set email alerts
|

Effects of polystyrene microbeads on cytotoxicity and transcriptomic profiles in human Caco‐2 cells

Abstract: Microplastics (MPs) pollution is a global paradigm that raises concern in relation to environment and human health. In order to investigate the molecular toxicity mechanisms of MPs, transcriptomic analyses were performed on in vitro Caco‐2 cell model. After observing that polystyrene microplastics (PS‐MPs) decreased cell viability in a dose‐dependent manner, the responsible genes and involved pathways that might make contribution to PS‐MBs‐induced toxicity to Caco‐2 cells were identified with Illumina RNA seq.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(63 citation statements)
references
References 50 publications
4
59
0
Order By: Relevance
“…In an in vitro model of human epithelial colorectal cells, researchers found that exposure to microplastics upregulated transcriptional factors involved in cell inflammation and proliferation. The chronic exposure to low doses of microplastics has the potential to induce epithelial cell injury and alterations to intestinal barrier function 134 . In a study of human lung epithelial cells, researchers found that exposure to inhaled polystyrene microplastics causes inflammatory and oxidative injury along with the disruption of intercellular junction proteins in the lung, potentially leading to pulmonary barrier dysfunction 135 …”
Section: Barrier Dysfunction and Its Role In Ad And Famentioning
confidence: 99%
“…In an in vitro model of human epithelial colorectal cells, researchers found that exposure to microplastics upregulated transcriptional factors involved in cell inflammation and proliferation. The chronic exposure to low doses of microplastics has the potential to induce epithelial cell injury and alterations to intestinal barrier function 134 . In a study of human lung epithelial cells, researchers found that exposure to inhaled polystyrene microplastics causes inflammatory and oxidative injury along with the disruption of intercellular junction proteins in the lung, potentially leading to pulmonary barrier dysfunction 135 …”
Section: Barrier Dysfunction and Its Role In Ad And Famentioning
confidence: 99%
“…(2019) and Rafiee et al (2018) in which translocation of PS particles from the gut was not observed and toxicologically relevant effects related to PS exposure were not found in vivo in rodents or in vitro in human intestinal epithelium 32 , 33 . Even more recently, however, several studies have suggested that microplastics can induce gut microbiota dysbiosis, intestinal barrier dysfunction, inflammation, and metabolic disorders in both mice and their offspring 34 46 .…”
Section: Introductionmentioning
confidence: 99%
“…Other sources of human exposure to MPs include commercial salt and bottled drinks, as well as airborne MPs that can be inhaled [ 77 ]. Although MPs have been detected in human stool samples [ 78 ], nanoplastics reportedly might decrease the viability of human Caco-2 cells [ 79 ], and they can induce pro-inflammatory responses [ 80 ]—adverse effects of MPs on human health have not been reported to date. Thus, studies of the effects of MPs on human health are still urgently needed.…”
Section: Resultsmentioning
confidence: 99%